Sources of variation evaluation of 24, 25(OH)2D levels and the ratio of 25OHD to 24, 25(OH)2D in apparently healthy Chinese adults: a multicenter cross-sectional study. Issue 192 (September 2019) - Yu, Songlin; Wang, Danchen; Yin, Yicong; Cheng, Qian; Xie, Shaowei; Yu, Jialei; Sun, Dandan; Cheng, Xinqi; Qiu, Ling
Highlights: 24, 25(OH)2 D and the 25OHD/24, 25(OH)2 D ratio were firstly evaluated in a Chinese population. Sources of variations in 24, 25(OH)2 D and the 25OHD/24, 25(OH)2 D ratio were studied. 24, 25(OH)2 D and 25OHD showed significant sex differences, but their ratio did not. Abstract: 24, 25(OH)2 D and the 25OHD/24, 25(OH)2 D ratio have recently been shown to be useful for screening for hypercalcemia caused by CYP24A1 mutations. However, no population-based data on 24, 25(OH)2 D have been published for Chinese populations, and few studies evaluated the sources of variation on 24, 25(OH)2 D levels and the 25OHD/24, 25(OH)2 D ratio. Hence, in 2018, we enrolled 1211 apparently healthy adults without systematic diseases from six representative cities in China (Beijing, Dongying, Guiyang, Urumqi, Shenzhen, and Qiqihar). 24, 25(OH)2 D and 25OHD levels were measured using isotope dilution liquid chromatography tandem mass spectrometry. Multiple regression analysis showed that sex contributed the most to variations in 24, 25(OH)2 D, 25OHD, and 25OHD/24, 25(OH)2 D (rp= -0.255, -0.253, and 0.141, respectively), and age also contributed to variations in 25OHD but not 24, 25(OH)2 D or 25OHD/24, 25(OH)2 D. Men had significantly higher 24, 25(OH)2 D and 25OHD levels than women, but had significantly lower 25OHD/24, 25(OH)2 D values. Individuals from Dongying had the highest 24, 25(OH)2 D and 25OHD values, whereas individuals from Urumqi had the lowest values. The median(2.5–97.5%) values for 24, 25(OH)2 D, 25OHD, and 25OHD/24, 25(OH)2 D were 1.2(0.36–2.65) ng/mL, 18.9(8.6–32.5) ng/mL, and 16.0 (9.8–30.8), respectively. 24, 25(OH)2 D was significantly correlated with 25OHD (r = 0.838, p  <  0.001), and 25OHD/24, 25(OH)2 D was significantly negatively correlated with 24, 25(OH)2 D (r = -0.758, P < 0.001) and 25OHD (r = -0.310, P < 0.001). In conclusion, in this nationwide, multicenter, cross-sectional study, we evaluated the levels of 24, 25(OH)2 D and the 25OHD/24, 25(OH)2 D ratio in the Chinese population. Sex contributed the most to variations in 24, 25(OH)2 D, 25OHD, and 25OHD/24, 25(OH)2 D.